Cost-Effectiveness Analysis of Metronidazole versus Metronidazole with Diloxanide Furoate in the Treatment of Amoebiasis in Ethiopia - Legese N; Aferu T; Kassa T (Dove Medical Press, 2021)
Nanati Legese,1 Temesgen Aferu,2 Tsehay Kassa3 1School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2School of Pharmacy, College of Medicine and Health Sciences, Mizan Tepi University, Mizan Aman, Ethiopia; 3Teklehaimanot health center, Addis Ababa, EthiopiaCorrespondence: Nanati Legese Email nanatilegese@yahoo.comIntroduction: Amoebiasis is one of the world's most prevalent and fatal infectious diseases. Several surveys revealed that amoebiasis is one of the most widely distributed diseases in Ethiopia. The combination of metronidazole with diloxanide furoate represents a new approach for the treatment of the infection.Objective: This study aimed to analyze the cost-effectiveness of diloxanide plus metronidazole compared with metronidazole alone in the treatment of amoebiasis in Ethiopia.Methods: An analytical decision model was used to analyze costs and effectiveness from a societal perspective by taking adult amoebic patients as the study population with a time horizon of two months. The potential impacts of uncertainty in single parameters were explored in one-way sensitivity analyses.Results: Metronidazole with diloxanide had a higher cost and effect compared to metronidazole alone with an incremental cost-effectiveness ratio (ICER) of 8 US$ per amoebic case cured. The result was sensitive to the decrease in the effectiveness of metronidazole with diloxanide.Conclusion: This study revealed the addition of diloxanide to standard treatment to be a more effective and more costly treatment strategy. Therefore, a decision for choosing the medication should be based on the ability of patients to pay for the treatment.Keywords: amoebiasis, metronidazole, metronidazole with diloxanide, cost-effectiveness analysis, Ethiopia